2019
DOI: 10.1038/s41598-019-45995-2
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Stability of the Ruminal Bacterial Communities in Beef Steers

Abstract: Nutritional studies involving ruminants have traditionally relied on relatively short transition or wash-out periods between dietary treatments, typically two to four weeks. However, little is known about adequate adaptation periods required to reach stabilization of the rumen microbiome that could provide more accurate results from nutritional studies in ruminants. This study determined the rumen bacterial communities and rumen environment parameters over ten weeks following transition from a forage-based to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…It may also be possible that the rumen microbiota simply needs longer to stabilize following dietary change. A recent study reported that it took approximately nine weeks for the rumen bacterial community composition of beef steers to stabilize following dietary adaptation from a pasture based diet to a corn/silage based diet supplemented with monensin [55]. As such, Clemmons et al [55] recommended adaptation or wash-out periods of at least eight weeks should be used in order to ensure stability of the rumen microbiota when performing nutritional intervention studies.…”
Section: Effect Of Diet and Time On Rumen Bacterial Compositionmentioning
confidence: 99%
“…It may also be possible that the rumen microbiota simply needs longer to stabilize following dietary change. A recent study reported that it took approximately nine weeks for the rumen bacterial community composition of beef steers to stabilize following dietary adaptation from a pasture based diet to a corn/silage based diet supplemented with monensin [55]. As such, Clemmons et al [55] recommended adaptation or wash-out periods of at least eight weeks should be used in order to ensure stability of the rumen microbiota when performing nutritional intervention studies.…”
Section: Effect Of Diet and Time On Rumen Bacterial Compositionmentioning
confidence: 99%
“…Moreover, parity may or may not influence rumen bacterial community, as Jewell et al (2015) [15] found high similarities between the first and second lactation cycles in terms of the bacterial community, whereas Pitta et al (2014) reported considerable differences between parities. Recently, Clemmons et al (2019) [16] reported that growing steers did not reach a stable bacterial community before an adaptation period of eight weeks. These reports have provided valuable insights into host specificity and the adaptation period to dietary transition.…”
Section: Introductionmentioning
confidence: 99%
“…Anderson et al (2016) found that rumen bacteria adapted faster to a diet with high concentrate. Less time for stabilization of a bacterial would improve productivity, because shifts in bacterial composition are associated with milk fat depression [19] and stable microbiomes improve host health [16]. Therefore, stabilization time would be another consideration for optimizing diet.…”
Section: Introductionmentioning
confidence: 99%
“…The only class found in Tenericutes is Mollicutes, of which some of the more notable members are Mycoplasma (Ludwig, Euzéby & Whitman, 2010). The differences observed in Tenericutes could possibly be the result of normal temporal fluctuations that occur in the rumen bacterial communities (Clemmons et al, 2019;Pitta et al, 2014). Additionally, one of the members of Tenericutes, Anaeroplasmataceae, also varied as a result of treatment group.…”
Section: Discussionmentioning
confidence: 97%
“…Changes in feeding behavior as a result of stocking density may have negative impacts on the rumen microbiome, as previous studies have found that decreased feed intake or feed restriction can alter the rumen microbial populations and communities (Firkins et al, 1987;McCabe et al, 2015). Although negative effects of overstocking can be observed on the behavior of dairy cattle within one to 2 weeks (Krawczel et al, 2012a), more time may be needed to observe more dramatic effects of stocking density on the rumen microbiome, as other research suggests that at least 6 weeks is required to observe transition to stable bacterial community composition (Clemmons et al, 2019). Alterations in the rumen microbiome of dairy cattle undergoing overstocking could have negative effects on feed efficiency and milk production (Jami, White & Mizrahi, 2014); thus, additional analyses with animals exposed to treatments for longer durations of time may yield more extensive changes to the rumen microbiome.…”
Section: Discussionmentioning
confidence: 98%